Methyl tert butyl ether targets developing vasculature in zebrafish (Danio rerio) embryos - Bonventre, Josephine A. (Aquat Toxicol, 2011)
Disruption of vascular endothelial growth factor (VEGF) signaling during early development results in abnormal angiogenesis and increased vascular lesions. Embryonic exposure to 0.625 to 10 mM methyl tert butyl ether (MTBE), a highly water soluble gasoline additive, resulted in a dose dependent increase in pooled blood in the common cardinal vein (CCV), cranial hemorrhages and abnormal intersegmental vessels (ISVs). The EC50s for the lesions ranked in terms of likelihood to occur with MTBE exposure were: pooled blood in the CCV, 3.2 mM [95 % CI: 2.2 – 4.7] > cranial hemorrhage, 11 mM [5.9 – 20.5] > abnormal ISV, 14.5 mM [6.5 – 32.4]. Organ systems other than the vascular system appear to develop normally, which suggests MTBE toxicity targets developing blood vessels. Equal molar concentrations (0.625 to 10 mM) of the primary metabolites, tertiary butyl alcohol (TBA) and formaldehyde, did not result in vascular lesions, which suggested that the parent compound is responsible for the toxicity. Stage specific exposures were carried out to determine the developmental period most sensitive to MTBE vascular disruption. Embryos treated until 6-somites or treated after Prim-5 stages did not exhibit a significant increase in lesions, while embryos treated between 6-somites and Prim-5 had a significant increase in vascular lesions (p ≤ 0.05). During the critical window for MTBE-induced vascular toxicity, expression of vegfa, vegfc, and flk1/kdr were significantly decreased 50, 70 and 40%, respectively. This is the first study to characterize disruption in vascular development following embryonic exposure to MTBE. The unique specificity of MTBE to disrupt angiogenesis may be mediated by the down regulation of critical genes in the VEGF pathway.